Kinetic factors differentiating mid-to-late sprint acceleration performance in sprinters and soccer players - Colyer, S. L.; Nagahara, R.; Takai, Y.; Salo, A. I. T. (ISBS Proceedings Archive (Michigan), 2018)
High-speed running in soccer is an important skill, however, the underlying kinetic factors are not fully understood. Ground reaction forces from steps 8 to 24 of maximal-effort sprints were captured for 24 soccer players and 28 track and field athletes using 54 force plates. Correlations between discrete force variables and horizontal acceleration were assessed, and statistical parametric mapping revealed performance associations across entire waveforms. Track and field athletes produced higher forces (mean anteroposterior: 1.56 N·kg-1) across shorter contacts (0.101 s) than soccer players (1.27 N·kg-1, 0.110 s). Interestingly, the technical ability to apply force and the performance-differentiating parts of stance were similar across groups. Thus, practitioners should perhaps target physical (force production) rather than technical factors to improve soccer players` sprint abilities.